Anticoagulation with or without antiplatelet therapy after transcatheter aortic valve replacement, when less is more: a meta-analysis. (25th November 2020) - Franchin, L; Vaira, M.P; Piroli, F; Angelini, F; Elia, E; Bocchino, P.P; Conrotto, F; D'Ascenzo, F; Giustetto, C; De Ferrari, G.M
Abstract: Background: About 40% of patients undergoing transcatheter aortic valve replacement (TAVR) have a history of atrial fibrillation (AF) and an additional 10% develop AF after TAVR. However, there is paucity of data regarding the optimal antithrombotic regimen following TAVR in patients with a clinical indication for oral anticoagulants (OAC). Purpose: To compare the prognostic impact of OAC plus at least one antiplatelet agent (APT) versus OAC therapy alone in patients undergoing TAVR. Methods: We systematically searched the literature for studies evaluating the comparative efficacy and safety of OAC + APT versus OAC alone in TAVR. Random-effect meta-analysis was performed comparing clinical outcomes between the two groups. All-cause mortality and cardiovascular mortality were the efficacy outcomes. Stroke and major bleeding, defined as Bleeding Academic Research Consortium bleeding types 3 to 5, constituted the safety outcome. Results: Overall, 398 titles and abstracts were identified through database searching. Four observational studies were selected, for a total of 1929 patients. After a median follow-up of 18.5 months (IQR 11.3–29.3), OAC + APT increased major bleeding events compared to OAC alone (OR=1.79; 95% CI 1.21–2.66; P=0.004) with no difference in stroke (OR 01.02; 95% CI 0.52–2.01; P=0.95), all-cause mortality (OR=1.07; 95% CI 0.78–1.47; P=0.66) and cardiovascular mortality (OR=1.08; 95% CI 0.79–1.47; P=0.62). Conclusion: A combination strategy of OAC + APT provides increased risk of bleeding compared to OAC therapy alone in patients undergoing TAVR with similar outcomes in terms of stroke, all-cause mortality and cardiovascular mortality; therefore, when feasible, it should be advised not to add APT on top of OAC therapy in patients without other clinical indications for APT treatment. Funding Acknowledgement: Type of funding source: None